Pengaruh Model Pembelajaran Student Team Achievement Division Berbantu Media Diorama Terhadap Hasil Belajar IPA - Pratiwi, Eva Aprilia Nur (Prosiding University Research Colloquium, 2021)
This study aims to determine the effect of the Student Team Achievement Division learning model assisted by Diorama media on science learning outcomes. This study was conducted on fifth grade students at SD N Payaman 1, Magelang Regency.This type of research is Pre Experimental Designs with the research design used One Group Pretest Posttest Design. The sample of this study was the fifth grade students at SD N Payaman 1, totaling 18 students. The sampling technique used in this research is saturated sampling. The method of collecting data was using multiple choice tests, then analyzed using the Piared Sample T-Test with the help of IBM SPSS Statistics 24.Based on the data analysis method used by the Paired Sample T Test, the Asymp Sig (2-tailed) is 0.000 and the t-count value is 14.028 > t table 1.734, so it can be concluded that Ho is rejected and Ha is accepted, which means that there is a positive and significant effect on the application of the learning model. Student Team Achievement Division on science learning outcomes for fifth grade students at SD N Payaman 1, Magelang Regency.